Playing with class: Middle‐class intensive mothering and the consumption of children's toys in Vietnam. (31st March 2017) - Le‐Phuong Nguyen, Khanh; Harman, Vicki; Cappellini, Benedetta
Abstract: This article explores the way in which Vietnamese mothers purchase, gift and share toys with their children. The study utilises a qualitative design comprising semi‐structured interviews with 10 Vietnamese middle‐class professional working mothers of children aged between 5 and 9. This research highlights the way in which toys defined as "good" by mothers need to fulfil a number of important practical and social functions: they act as an investment in the child's future, as a reward, and as a means for mothers to buy time for themselves. The findings illustrate how these functions are influenced by Confucian and Western discourses of intensive mothering, generating a localized style of middle‐class intensive mothering, characterized by what we have called the ideal of the triple excellent and intensive mother .